In vivo study of tetraprenyltoluquinone, an anticancer compounds from Garcinia cowa Roxb - Wahyuni, Fatma Sri; Lim, Siang Hui; Stanslas, Johnson; Lajis, Nordin; Hamidi, Dachriyanus (Wolters Kluwer - Medknow Publications and Media, 2017)
Objective: To investigate the in vivo antitumor effect of TPTQ against H-460 lung cancer cell lines in nude mice. Materials and Methods: Female nude mice bearing H-460 tumor at size approximately 5 mm in diameter were treated with a single intraperitoneal dose 800 mg/kg of TPTQ. The vehicletreated (10% tween 80) animals were used as control group. The tumor size and mice body weight were measured for 14 days. Results: Single treatment of 800 mg/kg of TPTQ displayed moderate antitumor activity against H-460 tumor xenografts as compared with vehicle-treated control. The mean time to reach RTV of 4 for vehicle-treated control group was 4.5 days whereas for TPTQ-treated (800 mg/kg) group was 9.5 days. Conclusion: The results showed that TPTQ slowed the tumor growth by 5 days. Thus, TPTQ may be considered as a promising compound in cancer chemotherapy.